A história de vida do hospedeiro pode intermediar respostas adaptativas a um patógeno emergente em anfíbios? - Mesquita, Andréa Ferreira Cussolim [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Host-generalist pathogens sporadically infect naïve hosts, potentially triggering epizootics. The frog killing-fungus Batrachochytrium dendrobatidis (Bd), which is linked to amphibian declines globally, is described as a host-generalist pathogen, infecting host species with varying life histories. Bd is a waterborne pathogen and has caused disproportionate population declines and extinctions of amphibians breeding in aquatic environments. Conversely, terrestrial amphibian species undergoing direct development in the forest leaf-litter are only sporadically exposed to Bd in the wild, and thus they may lack evolutionary responses against the pathogen. Here we tested whether terrestrial amphibian species show (i) higher infection loads and (ii) higher mortality rates than aquatic amphibians when experimentally exposed to Bd. We exposed three terrestrial and three aquatic amphibian host species to Bd (or clean water for the control group) in the laboratory. We swabbed individual frogs before and after the experimental infection and used qPCR analyses to quantify Bd infection loads from each individual host. We used a combination of Generalized Linear Mixed Models (GLMMs) and Parametric Survival Models (PSMs) to test for the effect of host developmental mode (aquatic vs. terrestrial) on both Bd loads and host mortality. We found that terrestrial amphibian species exposed to Bd showed higher infection loads than aquatic amphibian species. Terrestrial amphibians exposed to Bd also showed higher mortality rates than aquatic amphibian species. Our study shows a clear pattern of host life history triggering strong evolutionary responses against a widespread pathogen. Combined, our results provide novel information about the evolution of host responses to chytridiomycosis and contribute to the conservation of the globally endangered amphibians...

Patógenos generalistas esporadicamente infectam hospedeiros incomuns, potencialmente causando epizootia. O fungo Batrachochytrium dendrobatidis (Bd), associado a declínios globais de anfíbios, é descrito como um patógeno generalista, e infecta espécies hospedeiras com diversas histórias de vida. O Bd é um patógeno aquático e tem causado declínios populacionais e extinções incomparáveis em anfíbios que reproduzem em ambientes aquáticos. Em contrapartida, espécies de anfíbios terrestres com desenvolvimento direto em serrapilheira são expostos apenas esporadicamente ao Bd na natureza, e deste modo podem ser desprovidos de respostas evolutivas contra o patógeno. Neste estudo testamos se espécies de anfíbios terrestres exibem (i) carga de infecção e (ii) taxa de mortalidade maiores do que os anfíbios aquáticos quando expostos experimentalmente ao Bd. No laboratório, foram expostas três espécies hospedeiras de anfíbios terrestres e três de anfíbios aquáticos ao Bd (ou água inócua para o grupo controle). Realizamos swab dos indivíduos antes e depois da infecção experimental e utilizamos análises de qPCR para quantificar as cargas de infecção de Bd em cada hospedeiro. Combinamos modelos generalizados lineares mistos (GLMMs) e modelos paramétricos de sobrevivência (PSMs) para testar o efeito do modo de desenvolvimento do hospedeiro (aquático vs. terrestre) sobre a carga de infecção e mortalidade associadas ao Bd. Os resultados demonstraram que espécies de anfíbios terrestres expostas ao Bd apresentam maiores cargas de infecção do que as espécies de anfíbios aquáticos. Anfíbios terrestres também tiveram maiores taxas de mortalidade do que as espécies aquáticas. Nosso estudo revela padrões claros da história de vida do hospedeiro provocando fortes respostas evolutivas contra um patógeno amplamente disseminado. Combinados, os resultados proporcionam novas...
Keywords: Anfíbio; Tolerancia; Diatese; Amphibians